Humanitāri militārās intervences: Lībijas un Sīrijas gadījums - Birule, Agnija (Latvijas Universitāte, 2012)
Pētījuma mērķis ir atrast iekšpolitiskos faktorus, kas ietekmē starptautiskās sabiedrības lēmumu iejaukties Lībijas iekšpolitikā un nogaidīt ar militāra spēka lietojumu Sīrijas gadījumā. Pētījuma ietvaros analizēju Sīrijas un Lībijas intervences tipu un ārējo spēku stratēģijas. Analīzē lielāku vērību pievēršu abu intervenču militārajam un ne-militārajam raksturu, un mazāk fokusējos uz humanitārās intervences legalitāti. Man būtiski ir noskaidrot kāds ir ārējo spēku intervences fokuss Lībijā un Sīrijā un kāpēc ārējie spēki līdz pat 2012.gada 15.maijam nebija izlēmuši par militāra spēka lietojumu Sīrijā. Lībijas intervenci skatu laika posmā no 2011.gada 15.februārim līdz 2011.gada 31.oktobrim un Sīrijas intervenci no 2011.gada 15.marta līdz 2012.gada 15.maijam. Pētījumā izmantoju teoriju par humanitāri militārajām intervencēm, apskatu humanitāri militāro intervenču koncepta būtību un vietu starptautiskajā politikā, humanitāri militāro intervenču tipoloģiju un stratēģijas bastoties uz Teilora Seibolta intervenču dalījumu. Pamatojoties uz teorijas daļā apskatīto humanitāri militāro intervenču tipoloģiju un stratēģijām, pētījuma empīriskajā daļā, analizēju ārējo spēku iesaisti Lībijas un Sīrijas gadījumos. Tādejādi pētījums fokusējas uz Sīrijas un Lībijas intervences elementu apskatu, norādot uz tiem iekšpolitiskajiem faktoriem, kurus tālāk definēju kā ierobežojumus, tam lai izvērstu militāru akciju Sīrijā.

The main goal of this research paper is to determine factors at the state’s domestic level affecting the decision of international community to intervene into internal affairs of the Libyan state and use a military force at the last resort and avoid the use of military force into internal affairs of Syrian state when there is a real need for it. Within the framework of the master paper I analyze the type of humanitarian military intervention of both Libya and Syria and at the same time pay attention to the used intervention strategies by international community. Within analysis I mostly pay attention to the nature of military intervention determining its military or non-military involvement into affairs of another state. Research’s goal is not focus attention to the legal framework of intervention. I clarify the focus of humanitarian military intervention in Libya and in Syria and in such way try find an answer why international community made decision not to intervene in Syria by 15th of March, 2012. Humanitarian military intervention in Libya is analyzed during the period of 15th of February, 2011, to 31st of October, 2011, but intervention in Syria from the beginning of demonstrations dated back to 15th of March, 2011, to 15th of May, 2012. Research is based on the theory of humanitarian military interventions, reviewing the concept of humanitarian military intervention, explaining the typology and strategies of humanitarian military intervention according to the Taylor’s approach. Taking into analyses the typology and strategies of humanitarian military intervention in the empirical part of the research I analyze the involvement of international community into internal affairs of Syria and Libya with the aim to end up violations and mass murder in both countries. Thus research paper point out the factors at domestic level of both states defining them as restrictions for international community to intervene into internal affairs of another state with humanitarian intentions.
Human Military Interventions: The Case of Libya and Syria
Keywords: Politikas zinātne (politoloģija)